Freedom, Power and the Crisis of Politics in Revolutionary Yemen. Issue 3 (3rd July 2017) - Porter, Ross
Abstract: In the study of revolutionary events, it is often assumed that 'political crisis' attests to the failure of revolutionary ideals. Accordingly, revolution is understood as the pursuit of political consensus and the institutionalization of freedom and equality at the level of the state. In contrast, this article describes how, during the recent revolution in Yemen, revolutionaries actively negated proposals for a 'political solution.' It explores how the desire to contain power within the imaginary of 'the people' and safeguard revolutionary freedom produced instead an ethical charter for perpetuating a crisis of politics. As such, it argues that revolution should be understood less in terms of a seamless teleology of political development and more according to the immediate ethics of living a revolutionary life.